Optimalisasi Portofolio Nilai Saham: Studi Komparasi Kinerja Saham Syariah dan Nonsyariah - Ferry Khusnul Mubarok; Ahmad Ridho Darmawan; Zahirotul Luailiyah (Economica: Jurnal Ekonomi Islam, 2017)
The objective of this research is to analyze the comparison of sharia and nonsharia stock performance. The sample is a company listed on the Indonesia Stock Exchange, listing from 2013-2017. The sample consists of nonsharia stock (LQ45) and sharia stock (Jakarta Islamic Index). Sampling method used purposive sampling technique. Data analysis technique used Risk-Adjusted Return Measurement and analyzed by using paired sample T-Test. Based on analysis and discussion, there is no significant differences between portfolio performance of LQ45 and JII, either using Sharpe, Treynor, and Jensen alpha Index. Based on annual data, the performance of JII’s portfolio is better than LQ45 when macroeconomic is depression, while LQ45 portfolio performance is better when macroeconomic is booming. Thus, JII portfolios are more effective used when the economy is depressed, while LQ45 is more effective when the economy is booming.